Management of Missing Link in Kabupaten Bogor - Zulisan, Hafid (ASTONJADRO, 2023)
Bogor Regency is one of the regencies in West Java Province, with a central government located in the District of Cibinong. Bogor Regency consists of 40 subdistricts, of which 40 are cumulative after the division. Regarding the important role of the road network and public transport connectivity in the Bogor Regency, a problem called the missing link arises. The purpose of this study is reviewed from the aspects of road network performance, connectivity of activity centers, TOD areas and transportation nodes, then obtained by loading the Origin Destination Matrix (MAT) to the road network with the help of transportation modeling software using Saturn. Travel speed between cities / districts in Jabodetabek or origin of Bogor Regency does not reach the target speed of 40 km / hr, for Bogor District the average speed that occurs within the regency is 34.77 km / hr, so it is necessary to increase network capacity Street. The TOD area will have a missing link if the TOD has no connectivity with the mass transit node at a distance of more than 800 meters and is not on the main high-capacity mass transit line, such as the Cibinong TOD. The need for handling the missing link TOD area of the road network in the Greater Jakarta area, especially in the Cibinong area.